Diagnosis of preeclampsia: Antiangiogenesis, the new standard - Lacunza Paredes, Rommel Omar (2018)
The recent importance of antiangiogenic factors in the pathophysiology of preeclampsia and in the understanding of the multisystem manifestations of this disease is bringing closer the clinical application of laboratory values for the diagnosis, assessment of severity and prediction of preeclampsia. We will briefly review some recent examples in clinical application.